Investigating the most important aspect of elite grass court tennis: Short points. Issue 5 (October 2021) - Fitzpatrick, Anna; Stone, Joseph A; Choppin, Simon; Kelley, John
Research has shown that short points (points of 0–4 shots) are crucial in determining the outcome of elite men's and women's grass court tennis matches. However, research has not explored the importance of short points in more detail to inform practice design. This study aimed to establish the prevalence and importance of individual rally lengths within short points (i.e. points of 0, 1, 2, 3 and 4 shots) in terms of winning elite grass court tennis matches. Using the recently-validated PWOL ( Percentage of matches in which the Winner Outscored the Loser ) method, point-level data from 211 men's and 209 women's Wimbledon singles matches between 2015 and 2017 were analysed, with short points stratified into individual rally lengths. Results revealed that 1 shot (aces and missed serve-returns) was the most common rally length, with 0 shots (double faults) the least common. Points won of 1 shot, 2 shots and 4 shots were associated with winning matches and can therefore be considered important, but points won of 0 shots and 3 shots were not associated with match outcome. These results highlight the importance of serving and returning strategies at Wimbledon, and indicate that serves and serve-returns should be afforded focus during grass court training. However, the findings appear to contravene anecdotal assertions that 'serve plus one' strategies ( points won of 3 shots ) are crucial in elite tennis, as they did not differentiate winning and losing players; so coaches should consider the associated practice designs and amount of time afforded to such strategies.